PARTICIPATION OF GERMAN-MENNONITES IN TURKESTAN EXHIBITIONS AND FAIRS - J. X. Arzigulov (Web of Journals Publishing, 2024)
This article reveals the cooperation of the German mennonets with the Turkestan winter farm society through the analysis of the materials of various publications of archival sources.
Keywords: German-mennonets, vegetables, plums, Livestock, Show, cow, fruit, Saint, Caspian, Syrdarya, emigration, exhibition, viticulture, local crop, new variety, trade, Ashgabat market, farm.